Interpreting Kaomoji in the Momo Official Web Blog Comment Section: An Umberto Eco Analysis of Emotional Representation in Digital Communication - rahma julia; Maulluddul Haq (Universitas Negeri Padang, 2026)
Kaomoji is a form of nonverbal communication widely used in Japanese digital communication to express emotions and reinforce message meaning. This study aims to analyze the meanings of kaomoji used in the comment section of the Momo official web-blog based on Umberto Eco’s semiotic theory. This research employed a descriptive qualitative approach, which data consisting of comments containing kaomoji. Data were collected through observation and note-taking techniques and analyzed using Eco’s concept of semiosis by examining the relationship between signs, context, and interpretation. The findings reveal that the identified kaomoji represent various emotions, including positive emotions, negative emotions, and sadness with humorous nuances. Positive emotions were the most dominat category, indicating that kaomoji function to establish interpersonal closeness, strengthen affective expressions, and create a warmer communication atmosphere. The analysis also shows that the meanings of kaomoji are contextual and influenced by readers’ interpretations. Therefore, kaomoji function not merely as visual symbols but also as a system of signs that genereates meaning in digital communication. Kata Kunci: Kaomoji, semiotika Umberto Eco, web-blog, komunikasi digital